Experimental measurement and theoretical analysis on bubble dynamic behaviors in a gas-liquid bubble column. (16th January 2020) - Zhou, Yefeng; Kang, Panxing; Huang, Zhengliang; Yan, Pan; Sun, Jingyuan; Wang, Jingdai; Yang, Yongrong
Highlights: PTV and HSI techniques are employed to investigate the multiscale bubble dynamic behaviors. Bubble trajectory, bubble deformation and bubble rising velocity are correlated with bubble size. The accuracy of classical correlations in predicting bubble terminal velocities is quantitatively evaluated. How relative action intensity of gas and liquid phase influence radial distribution patterns of bubbly flow is revealed. A correlation is proposed to predict the width of gas-liquid interaction region. Abstract: Bubble dynamic behaviors have significant effects on the interfacial area between gas and liquid phases, the gas-phase residence time and the efficiency of heat and mass transfer. This study mainly investigated the single bubble dynamic behaviors and the radial distribution patterns of bubbly flow in a bubble column through Particle Tracking Velocimetry (PTV) and High Speed Imaging (HSI). As the results indicate, with the bubble size increasing, bubble deformation and bubble rising velocity are intensified and bubble trajectories change accordingly. Meanwhile, theoretically calculated values of single bubble terminal velocities are in accord with experimental values. According to the study, gas-liquid interaction has a noticeable impact on multiple radial distribution patterns of bubbly flow, including bubble size, velocity, the number of small bubbles and the width of gas-liquid interaction region. Finally, a correlation is proposed in this work to predict the width of gas-liquid interaction region based on a dimensionless analysis.